Determinants of Economic Growth in the Pre-Crisis Period - Ristanovic, Vladimir; Tasic, Nikola; Nikolic, Ivan (Industrija, 2018)
This paper analyses the determinants of economic growth in the post WWII to the pre-crisis period (1953-2007) using the dynamic generalized methods of moments (GMM) panel approach to determine effects of the real and the monetary determinants. Our results obtained from the panel of 61 countries suggest that economic growth varies between periods, as well as with level of economic development. Real determinants of GDP growth (real per capita GDP level, private consumption, investments, government expenditure, exports, and imports) affect the economic growth in all countries, while the monetary determinants (inflation, interest rate, and foreign direct investment) play more important role in the developed countries.
Keywords: Determinants of growth; GMM model; Economic Growth